Technological Advances of 3D Scaffold-Based Stem Cell/Exosome Therapy in Tissues and Organs - Gu, Chenyang; Feng, Jia; Waqas, Ahmed; Deng, Yushu; Zhang, Yifan; Chen, Wanghao; Long, Jun; Huang, Shiying; Chen, Lukui (Frontiers in Cell and Developmental Biology, 2021)
Regenerative engineering has made considerable progress in medicine. 3D scaffold is a typical representative product of regenerative medicine, due to different production methods, which can be made into different types to meet the structure and characteristics of tissues and organs. Stem cell therapy has been a fascinating advanced biomedical study in recent years, and it has prompted a lot of interest. However, due to the limitations and challenges of stem cell therapy, the use of exosome therapy can be used as an important way for regenerative medicine and clinical transformation. This article concludes the latest developments in stem cell therapy, exosome therapy and their combination therapy with 3D scaffolds in tissues and organs. Compared with stem cell therapy, 3D scaffold-based stem cell therapy can improve structure and function of several diseases in varying degrees. Besides, exosome therapy has the same therapeutic effects as stem cell therapy without negative effects. Thereby, 3D scaffold-based exosome therapy exhibits specialized therapeutic effects better without negative effects. 3D scaffold therapy provides hope for refractory and incurable diseases and becomes a turning point for the transformation of basic research into clinical translation.